Systematic mapping on structural testing criteria for concurrent programs considering dynamic aspects - Diaz, Silvia M. D.; Souza, Paulo S. L. de (Anais da Escola Regional de Alto Desempenho de São Paulo (ERAD-SP); 2017: Anais da VIII Escola Regional de Alto Desempenho de São Paulo, 2017)
As there are several approaches to define structural testing criteria for concurrent programs, it is necessary to describe the state of knowledge in this topic in order to identify the gaps that require to be addressed. Thus, it is fundamental to learn about who is investigating, which approaches and what purposes are there in current research, to evaluate which is the most effective path to follow to fill in divergences. Therefore, the goal of this systematic mapping is to find studies related to the testing of concurrent programs, that allows evaluating what is the best option to guide a research in the improvement of concurrent software quality through structural criteria. The results of the systematic mapping showed that there is indeed a gap in the definition of criteria for concurrent programs considering dynamic aspects.